2016
DOI: 10.1002/biof.1310
|View full text |Cite
|
Sign up to set email alerts
|

Methyl gallate, a potent antioxidant inhibits mouse and human adipocyte differentiation and oxidative stress in adipocytes through impairment of mitotic clonal expansion

Abstract: Methyl gallate (MG) is a derivative of gallic acid and a potent antioxidant. In this study, we confirmed that MG treatment effectively inhibits lipid accumulation, which occurred mostly in the early stages of adipogenesis. We also showed that shortly after adipogenic induction, MG facilitated a G0/G1 cell cycle arrest. Mechanistic studies revealed that MG treatment inhibited ERK1/2 phosphorylation, which is a key regulator of the G1- to S-phase transition. Furthermore, MG treatment prevented the adipogenic hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…At the highest concentration of 50 µg/mL, the lipid content of adipocytes was increased to 58% and 68% by compounds 2 and 3, respectively, while rosiglitazone at a concentration of 3 µM increased adipogenesis by 100%, compared with the vehicle control. However, in a recent study, an inhibition of lipid accumulation in the early stages of adipogenesis by methyl gallate has been reported [18]. In contrast, compound 4 did not exhibit a significant increase in adipogenesis ( Figure 2) despite its PPARγ agonistic action.…”
mentioning
confidence: 76%
“…At the highest concentration of 50 µg/mL, the lipid content of adipocytes was increased to 58% and 68% by compounds 2 and 3, respectively, while rosiglitazone at a concentration of 3 µM increased adipogenesis by 100%, compared with the vehicle control. However, in a recent study, an inhibition of lipid accumulation in the early stages of adipogenesis by methyl gallate has been reported [18]. In contrast, compound 4 did not exhibit a significant increase in adipogenesis ( Figure 2) despite its PPARγ agonistic action.…”
mentioning
confidence: 76%
“…Some of the phenolic antioxidants such as gallic acid and ellagic acid may prevent pre-adipocyte differentiation to adipocyte [53, 54]. The phenolic antioxidants gallic acid and ellagic acid present in Syzygium cumini seed powder could be responsible for the less adipose tissue deposition in high fat diet fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we reported that MG inhibits adipocytic differentiation of murine 3T3-L1 cells and human subcutaneous preadipocytes by delaying their mitotic clonal expansion via control of the expression of cell cycle-regulatory proteins in the early phase of adipogenesis [14]. In the present study, we found that MG can prevent b-catenin degradation during adipocytic differentiation and later can promote its stabilization and localization to the nucleus.…”
Section: Discussionmentioning
confidence: 63%
“…It was recently reported that MG has a significant anti-inflammatory effect on zymosan-induced inflammation in experimental arthritis by reducing neutrophil migration, production of inflammatory mediators, and activation of cells crucial for the development of this disease [12]. We previously demonstrated that MG inhibits adipocytic differentiation and reduces reactive oxygen species (ROS)-mediated oxidative stress by impairing mitotic clonal expansion [14]. Nevertheless, the molecular mechanisms underlying the inhibition of key adipogenic transcription factors have yet to be deciphered.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation